Digital habits of PR service-users: Implications for home-based interventions during the COVID-19 pandemic. (30th June 2020) - Polgar, Oliver; Aljishi, Maha; Barker, Ruth E; Patel, Suhani; Walsh, Jessica A; Kon, Samantha SC; Man, William DC; Nolan, Claire M
Remote models of pulmonary rehabilitation (PR) are vital with suspension of face-to-face activity during the COVID-19 pandemic. We surveyed digital access and behaviours and PR delivery preferences of current PR service users. There was significant heterogeneity in access to and confidence in using the Internet with 31% having never previously accessed the Internet, 48% confident using the Internet and 29% reporting no interest in accessing any component of PR through a Web-based app. These data have implications for the remote delivery of PR during the COVID-19 pandemic and raise questions about the current readiness of service users to adopt Web-based delivered models of PR.